The Profile and The Understanding of Science Process Skills Surakarta Open University Students in Science Lab Courses - Prajoko, Setiyo; Amin, Mohamad; Rohman, Fatchur; Gipayana, Muhana (Proceeding of International Conference on Teacher Training and Education, 2016)
The aim of this study is to find out the profile and the studentâs understanding about science process skill ofÂ Elementary School Teacher Study Program (Prodi PGSD), Teacher Training and Education Faculty, DistanceÂ Learning Business Unit Open University (UPBJJ-UT Surakarta). The study used a survey method byÂ spreading questionnaire to 65 students who join Science Lab Courses in April 2015. The Result of the studyÂ shows that the studentsâ profiles of PGSD program dominated by female and non-science graduates whoÂ work as non-civil servant teachers with 1-10 year job experience. Most of them have practical learningexperience but they have low understanding to the lab tools and materials. Students assume that the lab kitsÂ and modules that are used on the lesson are difficult to be understood. They also know the model of learningÂ and assessed aspects in the study. The result of science process skill measurement shows on mediumÂ category. Based on the result mentioned above, it is necessary to conduct further research by using modelsÂ and instructional media which are able to optimize the studentsâ science process skills.